2017
DOI: 10.1016/j.jimonfin.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers of U.S. unconventional monetary policy to emerging markets: The role of capital flows

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 47 publications
(45 reference statements)
4
69
0
Order By: Relevance
“…Several studies have investigated the international spillovers of US unconventional monetary policy to other countries (e.g., Ahmed & Zlate, 2014;Ahmed et al, 2017;Anaya et al, 2017;Barroso et al, 2016;Bowman et al, 2015;Chen et al, 2016;Fratzscher et al, 2016;Gambacorta et al, 2014;Georgiadis, 2016;Hausman & Wongswan, 2011;Rogers et al, 2014;Tillmann, 2016). This paper examines the spillovers of US conventional and unconventional monetary policies to Russian financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the international spillovers of US unconventional monetary policy to other countries (e.g., Ahmed & Zlate, 2014;Ahmed et al, 2017;Anaya et al, 2017;Barroso et al, 2016;Bowman et al, 2015;Chen et al, 2016;Fratzscher et al, 2016;Gambacorta et al, 2014;Georgiadis, 2016;Hausman & Wongswan, 2011;Rogers et al, 2014;Tillmann, 2016). This paper examines the spillovers of US conventional and unconventional monetary policies to Russian financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…There are also findings from vector auto regression (VAR) analysis suggesting that expansionary UMP shocks have positive impact on the real variables such as price and output (Gambacorta, Hofmann, & Peersman, 2014). Studies using global VAR models are also along the same lines (Anaya, Hachula, & Offermanns, 2017;Chen et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 92%
“…Anaya, Hachula, and Offermanns (2015) estimated a global VAR and found that the Fed's increase in balance sheet assets led to an increase in US portfolio outflows and EME portfolio inflows. As a result, EMEs lowered their policy rate.…”
Section: Related Literaturementioning
confidence: 99%
“…Krippner (2013), Lombardi and Zhu (2014), and Wu and Xia (2015) provided an estimated shadow interest rate to accommodate UMPs. 3 Gambacorta, Hofmann, and Peersman (2014) and Anaya, Hachula, and Offermanns (2015) identified UMP shock with an exogenous innovation to the Fed balance sheet. 4 Miyajima, Mohanty, and Yetman (2014) relied on decreasing US 10-year long-term bond yield and compressing US term premium to replicate UMPs.…”
Section: Baseline Impulse Responsesmentioning
confidence: 99%